Studi Pengaruh Volumetric Loading Rate Dan Upflow Velocity Terhadap Penurunan Parameter BOD,COD,TSS,dan Nitrat Dalam Limbah Cair Domestik Artificial Menggunakan Reaktor UASB - Ditto Himawan D.S (Jurnal Teknik Lingkungan, 2012)
Domestic waste which come from WC, i.e black water as well as other sources domestic waste has potensial to polute the environment because this waste has caracteristics high in BOD5 , COD, TSS, and Nitrate concentration. The purpose of this study is to find the concentration of artificial waste. if the concentration of the polutan is high, the load of the polutan in the waste also high. In this  study  Mixture of artificial grey water and black water were investigated. This Mixture consists of Biological Oxygen Demand (BOD5 ), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Nitrate (NO3). This research investigated the organic loading rate and upflow velocity variation parameters to treating the Mixture Grey Water and Black Water with reactor UASB. The decreasing Concentration of organic loading rate small varied BOD5  was about 102 mg/l , COD was about 287 mg/l, TSS was about 280 mg/l  and Nitrate was about 4 mg/l. Upflow velocity optimum 0,025 m/hour.